Covid-19: Sudden changes in the academic landscape and their impacts on quality of life in teaching work - Leite, Aline Chaves; Dornelas, Myriam Angelica (Seven Editora, 2023)
Faced with the pandemic scenario and the consequent sudden changes in the academic environment, teachers were significantly impacted by the need to adapt their teaching strategies when they needed to transfer their work environment into their homes. Thus, it is important to study the QWL of teachers in order to understand how and how much they were impacted and what measures can be adopted to mitigate these effects, since QoL and QWL can influence the quality of the education offered. Thus, the present study aimed to analyze the Quality of Life at Work of teachers of a public educational institution in the face of a pandemic scenario. This research was classified as qualitative and descriptive. Data collection took place through the collection of primary data that occurred through field research with the application of a semi-structured questionnaire, whose questions dealt with the characteristics of the profile of the respondents and the impacts of the pandemic on the QWL of teachers. The tabulation of the data was done through the digital platforms Google Forms   and Microsoft Excel 2013, where, through its resources, absolute numbers, percentages and the generation of graphs and tables were obtained. For qualitative research, content analysis was used. The partial results showed that the QWL of the professors surveyed was considerably impacted, especially due to the increased workload. It was concluded that the changes caused by the pandemic period negatively impacted the QWL of the respondents. The criteria of Work and total living space, working conditions and social integration in the organization stand out as the most impacted in the pandemic period. It is suggested, from the data collected, future studies on the investigated problem, for better understanding and mitigating suggestions.DOI:https://doi.org/10.56238/emerrelcovid19-041